The relationship between disease severity and functional status of post-covid-19 patients in Banda Aceh, Indonesia - Budi Yanti; Aulia Rahma Asril; Siti Hajar (Universitas Airlangga, 2022)
Introduction: Coronavirus Disease-2019 known as COVID-19 has spread rapidly worldwide, changing many aspects of life, including the functional status. Therefore, this study aims to assess the relationship between disease severity and the functional status of COVID-19 patients after recovery in Banda Aceh, Indonesia. Methods: A cross-sectional study was conducted with 109 post-COVID-19 patients who had been cured for more than 4-8 weeks in a Banda Aceh, Indonesia hospital. The history of disease severity of COVID-19 was collected from medical records. The functional status was assessed using the Post-COVID-19 Functional Status Scale (PCFS) questionnaire and divided into five categories: no functional limitation, negligible, slight, moderate, and severe. The relationship between the severity of COVID-19 and functional status was assessed statistically using the Spearman rank test. Results: Out of 109 selected respondents, there was one patient with mild severity, and 68, 37, and three patients have a history of moderate, severe, and very severe COVID-19, respectively. Those imply the functional status with no functional limitation (6%), negligible (21%), slight (4%), moderate (42%), and severe functional limitation (28%). In addition, fatigue was the most common symptom that persisted among respondents. Furthermore, the statistical result showed that the history of COVID-19 severity had a significant relationship with post-COVID-19 functional status (p<0.05). Conclusions: This study showed that post-COVID-19 cases have varying functional limitations ranging from negligible to severe. The COVID-19 severity significantly correlates with the functional status post-recovery. Hence, it is recommended to conduct a monitoring program to regularly assess the post-COVID-19 functional status, especially in outpatient clinics of the government healthcare center, to enhance the research findings.